Delta beta-Thalassaemia in Sicily: report of a case of double heterozygosity for A gamma delta beta-thalassaemia and A gamma G gamma delta beta-thalassaemia. Issue 1 (February 1983) - Musumeci, S; Romeo, M A; Pizzarelli, G; Schilirò, G; Russo, G
Abstract : A case of double heterozygosity for A gamma delta beta-thalassaemia and A gamma G gamma delta beta-thalassaemia was found during a screening programme in Sicily. The proband, a 4-year-old girl, showed a clinical picture of thalassaemia intermedia. Hb F (85.12% by the Singer method) was G gamma A gamma type. The parents and the brother were delta beta-thalassaemia carriers. Structural analysis of Hb F showed both G gamma and A gamma chains in the father, but only A gamma chains in the mother.